Understanding regulatory B cell development with single cell analyses - Meducator, The; Visva, Samantha; Oliveria, John-Paul; Zheng, Ruby (The Meducator, 2019)
There is very little research concerning human regulatory B cells and this may in part be due to their inconsistent responses to immunosuppressive cytokines such as IL-10. The purpose of this critical review is to examine our current understanding of regulatory B cell development, such as time points of differentiation, and how in silico computer modelling can improve this understanding. Specifically, bioinformatic analysis of the changes in cell surface markers and signalling molecules can help guide our understanding of the timing of cell-fate decisions and regulatory B cell differentiation. Tracking regulatory B cell trajectory with bioinformatics and in silico methods may improve our understanding of their role in many neurodegenerative diseases such as multiple sclerosis.